Modeling and computation in engineering II : proceedings of the 2nd SREE Conference on Modeling and Computation in Engineering (CMCE 2013), Hong Kong, 22-23 June 2013 /: proceedings of the 2nd SREE Conference on Modeling and Computation in Engineering (CMCE 2013), Hong Kong, 22-23 June 2013. (©2013) - Unknown
No abstract available